![image](https://tex.z-dn.net/?f=lim%28x%20-%3E%20%20%20%5Cfrac%7B%5Cpi%7D%7B6%7D%29%20%5Cfrac%7B%20%7B%20%5Ccos%7D%5E%7B2%7D%283x%29%20%7D%7B1%20-%20%20%5Csin%283x%29%20%7D%20%20%3D%20%20%7C%20%5Cfrac%7B0%7D%7B0%7D%20%7C%20%20%3D%20%20%7C%20%7B%20%5Ccos%20%7D%5E%7B2%7D%20%283x%29%20%3D%201%20-%20%20%7B%20%5Csin%7D%5E%7B2%7D%20%283x%29%20%20%3D%20%281%20-%20%20%5Csin%283x%29%20%29%281%20%2B%20%20%5Csin%283x%29%20%29%7C%20%20%3D%20lim%28x%20-%3E%20%20%20%5Cfrac%7B%5Cpi%7D%7B6%7D%29%20%5Cfrac%7B%281%20-%20%20%5Csin%283x%29%20%29%281%20%2B%20%20%5Csin%283x%29%29%7D%7B1%20-%20%20%5Csin%283x%29%7D%20%20%3D%20lim%28x%20-%3E%20%20%20%5Cfrac%7B%5Cpi%7D%7B6%7D%29%281%20%20%2B%20%5Csin%283x%29%29%20%3D%201%20%2B%201%20%3D%202)
\frac{\pi}{6}) \frac{ { \cos}^{2}(3x) }{1 - \sin(3x) } = | \frac{0}{0} | = | { \cos }^{2} (3x) = 1 - { \sin}^{2} (3x) = (1 - \sin(3x) )(1 + \sin(3x) )| = lim(x -> \frac{\pi}{6}) \frac{(1 - \sin(3x) )(1 + \sin(3x))}{1 - \sin(3x)} = lim(x -> \frac{\pi}{6})(1 + \sin(3x)) = 1 + 1 = 2" alt="lim(x -> \frac{\pi}{6}) \frac{ { \cos}^{2}(3x) }{1 - \sin(3x) } = | \frac{0}{0} | = | { \cos }^{2} (3x) = 1 - { \sin}^{2} (3x) = (1 - \sin(3x) )(1 + \sin(3x) )| = lim(x -> \frac{\pi}{6}) \frac{(1 - \sin(3x) )(1 + \sin(3x))}{1 - \sin(3x)} = lim(x -> \frac{\pi}{6})(1 + \sin(3x)) = 1 + 1 = 2" align="absmiddle" class="latex-formula">